Congenital Cytomegalovirus Prevention, Awareness and Policy Recommendations - A Scoping Study - Midgley, Georgia; Smithers-Sheedy, Hayley; McIntyre, Sarah; Badawi, Nadia; Keogh, John; Jones, Cheryl A. (Infectious Disorders - Drug Targets, 2020)
Background: Congenital cytomegalovirus (cCMV) is known to cause childhood deafness, neurodevelopmental disability and death. Simple hygiene precautions are effective in reducing maternal risk of CMV infection. Objective: To review i) awareness of CMV infection and available primary prevention strategies both in the community and amongst health professionals ii) available cCMV information sources in the literature, grey literature and published professional guidelines. Methods: Scoping study to i) identify literature pertaining to cCMV awareness amongst parents and health professionals using MedLine and CINAHL databases via EBSCO ii) review one high income country’s guidelines and recommendations regarding cCMV infection and pregnancy (example country Australia) iii) grey literature for parental information. Results: Worldwide awareness of cCMV and of available prevention strategies amongst women and health professionals are poor. Findings internationally suggest at least half of maternity care health professionals do not routinely provide advice to women regarding simple hygiene precautions that can reduce their risk of infection during pregnancy. Though information resources regarding cCMV are available, they are frequently not included within general healthy pregnancy advice and require individuals to search for ‘congenital cytomegalovirus’. Conclusion: cCMV is a preventable cause of serious congenital disability and death. Prevention opportunities are being missed because most women are not aware of cCMV or how to reduce their risk of infection in pregnancy, in part due to poor health professional awareness. New strategies to disseminate cCMV information to the community and to support health professionals to embed cCMV advice within routine pregnancy counselling is required.
Keywords: Congenital cytomegalovirus